2021
DOI: 10.1021/acsomega.0c05237
|View full text |Cite
|
Sign up to set email alerts
|

Cesium-Catalyzed Hydrogen Production by the Gasification of Woody Biomass for Forest Decontamination

Abstract: The large quantities of contaminated wood produced following the radioactive cesium decontamination of forests after the Fukushima Daiichi Nuclear Power Plant accident in 2011 can be used as a biomass resource for energy production via thermal treatment (e.g., gasification). To store the radioactive Cs ash produced from gasification, the immobilization of Cs in the pollucite structure is possible and requires stable Cs additives. In this study, a Cs additive (Cs 2 CO 3 , CsCl, CsNO 3 , or Cs 2 SO 4 ) was doped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The increase of reaction temperature enhanced the rate of cracking and therefore the yield of gas increased. The study by Koido et al 95 showed that the production of H 2 was enhanced by metal salts. They selected Cs 2 CO 3 , CsCl, CsNO 3 and Cs 2 SO 4 as catalysts for the gasification of timber waste in a fixed-bed downdraft-type continuous steam gasification process at 800 °C.…”
Section: Biorefinery Based On the Thermochemical Treatment-commercial...mentioning
confidence: 99%
“…The increase of reaction temperature enhanced the rate of cracking and therefore the yield of gas increased. The study by Koido et al 95 showed that the production of H 2 was enhanced by metal salts. They selected Cs 2 CO 3 , CsCl, CsNO 3 and Cs 2 SO 4 as catalysts for the gasification of timber waste in a fixed-bed downdraft-type continuous steam gasification process at 800 °C.…”
Section: Biorefinery Based On the Thermochemical Treatment-commercial...mentioning
confidence: 99%